2002
DOI: 10.1177/019263650208663305
|View full text |Cite
|
Sign up to set email alerts
|

Involving Students in Violence Prevention: Anonymous Reporting and the Need to Promote and Protect Confidences

Abstract: Researchers queried school counselors throughout the United States 2 months prior to and 2 months following the April 1999 Columbine (CO) High School shootings. The counselors were asked whether or not they would breach a student's confidentiality in 26 specific scenarios. The "before" and "after" groups were demographically similar but differed significantly in their predictions as to whether or not they would breach confidentiality. Resultsfrom two focus groups on school violence prevention provide recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…Results also revealed that middle-school counsellors rated 'Likelihood that student will continue counselling after breaking confidentiality', 'Duration of the risk-taking behaviour', and 'Age of the student' significantly higher than high-school counsellors did, with small effect sizes. These results seem to be consistent with previous studies (Jenkins & Palmer, 2012;Moyer et al, 2012;Stone & Isaacs, 2002) where SCs were more likely to breach confidentiality with younger students. This might be attributed to mandatory reporting laws (Turkish Criminal Law, 2004) concerning children under 15 years of age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results also revealed that middle-school counsellors rated 'Likelihood that student will continue counselling after breaking confidentiality', 'Duration of the risk-taking behaviour', and 'Age of the student' significantly higher than high-school counsellors did, with small effect sizes. These results seem to be consistent with previous studies (Jenkins & Palmer, 2012;Moyer et al, 2012;Stone & Isaacs, 2002) where SCs were more likely to breach confidentiality with younger students. This might be attributed to mandatory reporting laws (Turkish Criminal Law, 2004) concerning children under 15 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…Another study (Sivis-Cetinkaya, 2018) conducted with a Turkish sample cites female SCs as being more likely to uphold school and district policies, and to prioritise avoiding legal problems for the student in reporting risk-taking behaviours to parents. A difference between SCs' reporting behaviour with respect to school level of employment was cited in some former American studies (Jenkins & Palmer, 2012;Moyer et al, 2012;Stone & Isaacs, 2002), with middle-school counsellors being more likely than their high-school counterparts to report students' risk-taking behaviours. The role of other demographic variables in SCs' reporting of students' risk-taking behaviours, such as attending mandatory in-service training, is yet to be addressed in the international scientific literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Part of the current study was designed to assess the possible differences between student and teacher perceptions. Although actual violent behaviors were not accounted for in the current study, the perceptions from various groups of people can be important (Skiba et al, 2006;Stone & Isaacs, 2002). It is possible that different individuals within the same school have different perceptions of school climate due to the differences in their experiences, perspectives, or roles in the school structure.…”
Section: Perceptions Of School Safety and Violencementioning
confidence: 91%
“…Although little research has directly examined the perspectives of students and teachers on violence prevention, some research has suggested that student perceptions more realistically represent the problematic behaviors within the school environment than adults' perceptions (Stone & Isaacs, 2002). These findings underscore the need to further examine the perceptions of teachers and students on school safety.…”
Section: Perceptions Of School Safetymentioning
confidence: 99%
“…The alleged plan was foiled when a classmate heard their discussions and notified authorities. Stone and Isaacs (2002) report that research identifies the following conditions as necessary to encourage and facilitate student reporting: 1) an anonymous reporting mechanism; 2) confidentiality procedures; 3) student choice of counselor; and 4) a properly educated faculty and staff about school safety.…”
Section: Literature Reviewmentioning
confidence: 99%